Aisha Bakes Kukis / Wan Nor Aishah Wan Kamaruzaman - Wan Kamaruzaman, Wan Nor Aishah (2021)
AishaBakesKukis Sdn Bhd is a business that has been registered under the Go-E Commerce that falls in the food and beverage category. The products that we produce are variety of cookies. The name of AishaBakesKukis came from the combination of the founder and her hobby which is baking. Hence, the formation of our business name. Our business was first established in November 2020 and is based in Seri Manjung, Perak. We are located specifically at No. 1, Medan Selera Manjung, 32040 Seri Manjung, Perak. Though we are based in Seri Manjung, Perak. We are still taking orders from the other state since we do postage and delivery to nearest area in Manjung. For marketing purposes, we mainly use our social media platform to attract and engage with our customers from various backgrounds which is Facebook. We frequently post updates like teasers, announcements, any soft and hard sell advertisings in our page. These interactions help us view the bigger picture on how to properly give exposure to our products as well as brand. AishaBakesKukis’s marketing strategy includes emphasizing the quality and price of products as well as services. We tend to offer a normal range of price for our product as it serves as a strategy to stand out from our competitors. One of the main factors for establishing a business is that it contributes to the effect of a well-grown business. Based on the location of AishaBakesKukis this eventually makes it easier for us to expand as a business. A lot of people venture into business due to its high acceptability from customers. Our business is also relevant in the area due to how acceptance of Cookies is as a food, dessert as well as a side dish where no specific type of people is needed to become our customers. Hence, our prospect is to ensure that our product is known by the customers by producing only goods that reach our par.